P3.342 Sex and the 2012 Olympics Part 2. Prospective Study of the Impact of Olympic Visitors on Specialist STI Services in London and Weymouth and on STIs Diagnosed. (13th July 2013) - Brook, G; Hall, V; Hughes, G; Marsh, K; Hartley, A; Foster, R; Crook, P; Coyne, K; Mercer, C; Cassell, J
Abstract : Background: Predicting the impact on services is essential for managing large public events. Objectives: To measure the impact of the Olympics on STI services Methods: Between 20 Jul-16 Sept 2012, new registrants at STI clinics in London and Weymouth were asked to complete a survey to determine if they were visitors to the Olympics from the UK and abroad. Survey responses were linked to the national specialist STI clinic activity dataset (GUMCAD) Results: Provisional data show that 24/35(69%) clinics returned 12347 surveys. Among respondents, 11158(90%) were local residents, 1081(9%) non-Olympic visitors and 108(0.9%) Olympic visitors (OV). Survey participation was 12347/37704(33%). Most OVs were seen in central London clinics (52, 48%) and Weymouth (21, 19%), with the majority (66, 61%) attending during the Olympics (27 Jul-12 Aug). The percentage of new registrants who were OVs reached a maximum of 9% per week in one London clinic and 21% per week in Weymouth Among OV respondents, 37 (35%) were non-UK residents and 59(55%) were Olympic workers. Compared with locals, OV were more likely to be male (74% vs 59%), in the 15–24 age range (44% vs 36%) and ethnically white (83% vs 68%). There were no differences in sexual orientation but a higher prevalence of acute STIs among OVs (12/108, 11.1%) vs locals (950/11158, 8.5%) was reported. A total of 30 STIs were diagnosed among OVs including NSU (10, 9%), chlamydia (5, 5%), warts (5, 5%), herpes (4.4%), gonorrhoea (3.3%), molluscum (2.2%) and scabies (1.1%) Conclusions: For the first time in the history of the Olympics, the impact of visitor attendance at sexual health clinics has been measured prospectively. OV were seen in substantial numbers only during the Games and had comparable STI rates to locals. These data will prove valuable in planning future sexual health services for cities with large-scale events